2001
DOI: 10.1353/aad.2012.0206
|View full text |Cite
|
Sign up to set email alerts
|

Deaf College Students' Reading Comprehension and Strategy Use

Abstract: Two comprehension studies were conducted with 46 deaf college students. In the first, 20 deaf college students representing higher and lower reading-ability levels were tested for correctly stating the main idea of a passage, answering content questions, indicating their understanding of the words and phrases, and recognizing a topically incongruent sentence embedded in the passage. The results suggest that deaf students profess a better understanding of what they read than they are able to demonstrate. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
11

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 27 publications
1
19
0
11
Order By: Relevance
“…In general, DHH students appear to be relatively poor at assessing their reading comprehension and often consider themselves to be good readers even when they are largely unaware of what that means (Ewoldt 1986;Kelly, Albertini, and Shannon 2001). Teachers and parents may inadvertently foster such behaviours in young DHH readers by underestimating their reading abilities and thus demonstrating in the literacy domain the over-directiveness often seen among hearing adults interacting with DHH children.…”
Section: Metacognitionmentioning
confidence: 99%
“…In general, DHH students appear to be relatively poor at assessing their reading comprehension and often consider themselves to be good readers even when they are largely unaware of what that means (Ewoldt 1986;Kelly, Albertini, and Shannon 2001). Teachers and parents may inadvertently foster such behaviours in young DHH readers by underestimating their reading abilities and thus demonstrating in the literacy domain the over-directiveness often seen among hearing adults interacting with DHH children.…”
Section: Metacognitionmentioning
confidence: 99%
“…The greatest differences between the better and less-skilled readers were found in their evaluating comprehension. As in the Gibbs (1989) and Kelly, Albertini, and Shannon (2001) studies, there was no hearing comparison group, but only one of the 11 participants was found to be at the highest level of performance in terms of the quantity and quality of metacomprehension strategies reported. In general, then, deaf students from secondary school through university appear to have relatively limited metacognitive awareness with regard to reading, but rarely have they been compared to same-aged hearing students.…”
Section: Introductionmentioning
confidence: 95%
“…Participants were not asked to indicate how they would correct or overcome those problems. Kelly, Albertini, and Shannon (2001) examined the extent to which deaf students were able to identify the main ideas of academic texts and their awareness of whether or not passages made sense. Two groups of deaf university students, one reading at the eighth grade level and one reading at the ninth grade level, proved to be extremely poor in both respects.…”
Section: Introductionmentioning
confidence: 99%
“…Kelly et al's research (2001) on the use of reading strategies by deaf college students found that deaf and hard of hearing readers of higher ability benefit more from different reading strategies than readers of lower ability. Teachers are responsible for planning differentiated instruction based on reading ability (Kelly et al, 2001). The study also indicated that teachers should focus on the following strategies: determining the meaning of text rather than vocabulary (word by word), synthesizing the main idea, promoting background knowledge references and relating to new knowledge, using authentic text, and developing an idea of coherence (Kelly et al, 2001).…”
Section: Literacy Strategiesmentioning
confidence: 99%
“…For example, a strategy could include inserting random sentences in text passages in order for students to practice finding sentences that do not make sense or belong in the text (Kelly et al, 2001). This is an important strategy to enhance the learning experience of deaf and hard of hearing readers.…”
Section: Literacy Strategiesmentioning
confidence: 99%